2022
DOI: 10.1152/ajplung.00084.2022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nebulized epoprostenol and iloprost on hemoglobin oxygen affinity: an ex vivo experiment

Abstract: Background Inhalational prostacyclins act as strong vasodilators, potentially improving oxygenation by reducing shunt fraction and ventilation-perfusion mismatch. As prostacyclin receptors are known to be present on human erythrocytes, possible direct effects on oxygenation were further explored by examining the sole in-vitro influence of prostacyclins on hemoglobin oxygen (Hb-O2) affinity. Methods Venous blood samples from 20 healthy volunteers were exposed in-vitro to supramaximal doses of epoprostenol, ilop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Immediately after blood sampling, the heparinized samples were stored on ice, while blood gas analysis (ABL 800 flex, Radiometer) was performed from aliquots. Another aliquot was separated and stored at − 80 °C for the quantification of 2,3-bisphosphoglycerate (2,3-BPG) and adenosine triphosphate (ATP) concentrations with a validated liquid chromatography–tandem mass spectrometry method described before 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after blood sampling, the heparinized samples were stored on ice, while blood gas analysis (ABL 800 flex, Radiometer) was performed from aliquots. Another aliquot was separated and stored at − 80 °C for the quantification of 2,3-bisphosphoglycerate (2,3-BPG) and adenosine triphosphate (ATP) concentrations with a validated liquid chromatography–tandem mass spectrometry method described before 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Woyke et al exposed venous blood samples from healthy volunteers to the pulmonary vasodilators epoprostenol and iloprost (119). With epoprostenol, they detected an increased Hb-O 2 affinity in all subgroups under laboratory conditions, however, further research is required to validate this effect in vivo.…”
Section: Nebulized Epoprostenolmentioning
confidence: 99%
“…Finally, drugs used for treatment might cause P 50 changes. Recently, Woyke et al [ 15 ] demonstrated in in vitro experiments that nebulized epoprostenol (a potent vasodilatory prostaglandin) significantly decreased P 50 by approximately 3 mmHg thereby increasing Hb-O 2 affinity. As inhaled epoprostenol is also used for the treatment of COVID-19 ( Identifier: NCT04452669, accessed on 8 June 2022), it would be of interest to know whether patients in the study by Ceruti and colleagues were on epoprostenol treatment.…”
mentioning
confidence: 99%